Proceedings of the 38th Annual Hawaii International Conference on System Sciences
DOI: 10.1109/hicss.2005.1
|View full text |Cite
|
Sign up to set email alerts
|

"Turn Off the Television!": Real-World Robotic Exploration Experiments with a Virtual 3-D Display

Abstract: In order to apply mobile robots to a new range of applications, we require control architectures and interfaces that support symbiotic interaction. Remote deployment of mobile robots offers one of the most compelling opportunities to merge human intelligence with machine proficiency. This paper discusses a mixedinitiative control strategy based not on video, but on an abstracted, collaborative workspace-a 3-D, video-game representation constructed on-the-fly-that promotes situation-awareness and efficient task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…The perceived ease of use and perceived performance were the highest for ME3D and the lowest for VC2D. The results corroborate previous research findings, for example, [109][110][111][112][113].…”
Section: Pilot Interface Designsupporting
confidence: 82%
“…The perceived ease of use and perceived performance were the highest for ME3D and the lowest for VC2D. The results corroborate previous research findings, for example, [109][110][111][112][113].…”
Section: Pilot Interface Designsupporting
confidence: 82%
“…Another insight was that adding bandwidth to the interface did not necessarily enhance performance. In one study operators with a map-based interface did equally well at the task of exploring a building as operators who got the same map, but were also given a video-based interface which required 5000 times more bandwidth [5]. In fact, operators with more data made more errors and felt more frustrated.…”
Section: Introductionmentioning
confidence: 98%
“…User trust is a major component in operational success, and in our studies trust has been shown to be reduced by conflicts regarding the user's assumptions with respect to robot initiative [5]. Nourbkhsh [7] states "robots are real things, robots push back on the world," unless left on their own, i.e., fully autonomous, they will always be interacting in social spaces [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, these are subject to false alarms and multipart problems in some environments. New technologies, such as the microwave radiomater 10 are promising but have not yet reached a maturity level suitable for deployment.…”
Section: Human Presence Detectionmentioning
confidence: 99%